2005
DOI: 10.1177/0306624x04272981
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Needs and Behavioral Risk Factors of HIV-Positive Inmates

Abstract: Considerable research has found inmates to be at high risk for HIV/AIDS. Furthermore, research has shown additional HIV/AIDS threats faced by females in the general population and especially by those incarcerated. Behavioral interventions and educational programs have been developed based on these studies. However, few empirical studies have examined the self-expressed needs of HIV-positive inmates or the degree to which inmates' needs are gender specific. This pilot study compares the needs of HIV-positive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Ninety-three percent of all U.S. state prisoners are male (Harrison & Beck, 2006), and at year end 2004, 1.9% of male state prisoners were known to be HIV positive (Maruschak, 2006). However, because HIV-testing policies in prisons vary by jurisdiction and not all prisoners are required to test for HIV, the actual prevalence of infection is likely to be higher than reported (Lanier & Paoline, 2005).…”
mentioning
confidence: 99%
“…Ninety-three percent of all U.S. state prisoners are male (Harrison & Beck, 2006), and at year end 2004, 1.9% of male state prisoners were known to be HIV positive (Maruschak, 2006). However, because HIV-testing policies in prisons vary by jurisdiction and not all prisoners are required to test for HIV, the actual prevalence of infection is likely to be higher than reported (Lanier & Paoline, 2005).…”
mentioning
confidence: 99%
“…Even among male inmates with HIV/AIDS, there is reason to believe that some inmates who did not participate in the program (e.g., inmates who were unaware of or unwilling to disclose their HIV status, were not seriously ill, or were unwilling to acknowledge their illness) were likely to have been experiencing fewer symptoms than participants in the program, whereas other inmates who were either released or transferred before they could be identified may have been even more vulnerable than the inmates described in this report. For example, Lanier and Paoline (2005) reported a lower prevalence of need for many of the services described here in an assessment of HIV-positive inmates at jails in Duval County (Jacksonville, Florida), particularly with regard to medical care and support services (particularly case management and legal services). However, inmates described in that study were not necessarily symptomatic at the time of the assessment, and therefore, they were less likely to be in immediate need of most health care services.…”
Section: (Continued)mentioning
confidence: 91%
“…Studies have found that drug users, regardless of their incarcerated status, are less likely to adhere to ARV medication regimens than substance non-users, and that HIV treatment disruption is particularly high in periods of relapse (Malta, Strathdee, Magnanini, & Bastos, 2008). Moreover, psychological and substance use disorders are known to be correlated with unstable living situations (Lanier & Paoline, 2005; Meyer, Chen, & Springer, 2011; Phillips, 2011; Rebholz, Drainoni, & Cabral, 2009). Studies have consistently shown that an unstable living situation is one of the most prominent barriers to continued HIV treatment during the transition home from incarceration (Lanier & Paoline, 2005; Meyer et al, 2011; Nunn et al, 2010; Rich et al, 2001).…”
Section: The Importance Of Continuous Hiv Carementioning
confidence: 99%